2005
DOI: 10.1097/00002820-200509000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Symptom, Symptom Experiences, and Symptom Distress Encountered by Women With Breast Cancer Undergoing Current Treatment Modalities

Abstract: Adjuvant chemotherapy protocols used to treat women with breast cancer have evolved over the last decade and have dramatically altered the symptoms and symptom experiences of these women. The purpose of this study was to identify symptoms, symptom experiences, and resulting symptom distress encountered by women with breast cancer undergoing surgery and receiving current chemotherapy protocols. Convenience sampling was used to recruit 20 women for this study. Women were asked to tell their story and transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(106 citation statements)
references
References 10 publications
10
93
0
3
Order By: Relevance
“…Firstly, chemotherapy-induced hair loss is considered to be the most important side effects of chemotherapy, frequently ranking among the first three for breast cancer patients [16,19,25,26,29,30,39] and can lead to refusal of chemotherapy [3,20]. Secondly, it is described by breast cancer women as causing distress and as being traumatizing [5,[8][9][10][11]13,31,35,36]. Thirdly, there might be an impact on body image [17,40] although not all studies reported this association [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, chemotherapy-induced hair loss is considered to be the most important side effects of chemotherapy, frequently ranking among the first three for breast cancer patients [16,19,25,26,29,30,39] and can lead to refusal of chemotherapy [3,20]. Secondly, it is described by breast cancer women as causing distress and as being traumatizing [5,[8][9][10][11]13,31,35,36]. Thirdly, there might be an impact on body image [17,40] although not all studies reported this association [14].…”
Section: Discussionmentioning
confidence: 99%
“…Patients described hair loss as traumatizing and distressing [5,[8][9][10][11]13,35,36]. Indeed, it was described as harder than losing a breast [3,13].…”
Section: Relative Importance Of Hair Loss Among Chemotherapy-related mentioning
confidence: 99%
“…Moreover, supplementary treatment in breast cancer patients may introduce additional health and appearance distortions relevant for body image. Among these, hair loss strongly impairs body esteem, although it depends on the attitude to this problem the woman adopts (Baxley, Kendrick, & Brown, 1984;Boehmke & Dickerson, 2005). While some women view their hair loss as a sign of courage and a source of pride, others perceive it as a traumatic experience seriously undermining their identity.…”
Section: Introductionmentioning
confidence: 99%
“…Breast biopsy, lumpectomy, and mastectomy often induce psychological distress, pain, and, mainly due to anesthesia, nausea and vomiting. [3][4][5][6][7] Chemotherapeutic and radiotherapeutic breast cancer treatment are strongly associated with psychological distress, fatigue, and, in the case of chemotherapy, nausea and vomiting. [8][9][10] Substantial psychological distress is present in 1 out of every 3 breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%